COLLABORATIVE WRITING IN ENHANCING ESSAY WRITING FOR THE FOURTH SEMESTER AT POLYTECHNIC ALKON KALIMANTAN - Rochman, Muhammad; Widjajanti, Suzanna; Ningsih, Era Wahyu (Faculty of Letters Universitas Balikpapan, 2025)
Collaborative writing offers a powerful pedagogical approach that significantly enhances essay writing skills. By encouraging students to work together, it fosters a dynamic environment where diverse perspectives and knowledge converge to create more robust academic work. This shared intellectual journey moves beyond solitary writing, promoting clear articulation, active listening, and effective negotiation of meaning. Brainstorming in groups sparks innovative ideas and arguments, while providing and receiving constructive feedback deepens understanding of rhetoric and argumentation. Students become more attuned to their audience, collectively striving for clarity and persuasive impact. Ultimately, collaborative writing not only yields higher-quality essays but also cultivates essential teamwork, communication, and critical thinking skills applicable beyond academia, leading to students’ improvement. A qualitative study explored the impact of collaboratively designed materials on college students' English writing. The research revealed a significant students’ improvement in their writing, marked by richer ideas and expanded vocabulary, compared to previous individual learning. Notably, student participation in collaborative writing sessions also increased, suggesting a positive correlation between this approach and learning motivation. The findings indicate that collaborative learning in a professional context can effectively boost engagement and enhance the quality of students' written work, contributing to overall students’ improvement in their writing skills.